Estimation of carbon sequestration of undergrowth and litter in post-burn and unburned peatland in agrosilvofishery demonstration plots, Sepucuk, Ogan Komering Ilir - Prayitno, Muh Bambang; Saputra, Bony Dwi (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2024)
The research aimed to estimate biomass and carbon sequestration in unburned and post-burn peatlands. Data analysis was conducted from January 2023 to February 2023 in Sepucuk Agrosilvofishery Peatland Restoration demonstration plots, Ogan Komering Ilir, South Sumatra. The biomass and litter of understory vegetation were observed in good, medium, and poor vegetation conditions using the destructive method on 0.5 m x 0.5 m observation plots with 3 repetitions, and with 3 repetitions for each vegetation condition. The research depicts that post-burn peatland has a higher average carbon storage of understory vegetation and litter, 1.95 tons/ha for understory vegetation and 0.50 tons/ha for litter. However, unburned peatland has lower average carbon storage, 0.80 tons/ha for understory vegetation and 0.47 tons/ha for litter. The comparison depicts that Purun and Sembangun understory vegetation samples have significantly different results, while the vegetation litter samples have insignificantly different results.